HMGB1 Increases IL-1β Production in Vascular Smooth Muscle Cells via NLRP3 Inflammasome - Kim, Eun Jung; Park, So Youn; Baek, Seung Eun; Jang, Min A.; Lee, Won Suk; Bae, Sun Sik; Kim, Koanhoi; Kim, Chi Dae (Frontiers in Physiology, 2018)
Vascular smooth muscle cells (VSMCs) are the major cell type in the blood vessel walls, and their phenotypic modulation is a key cellular event driving vascular remodeling. Although high mobility group box-1 (HMGB1) plays a pivotal role in inflammatory processes after vascular injuries, the importance of the links between VSMCs, HMGB1 and vascular inflammation has not been clarified. To prove the hypothesis that VSMCs might be active players in vascular inflammation by secreting inflammatory cytokines, we investigated the proinflammatory effects of HMGB1 and its intermediary signaling pathways in VSMCs. When cultured human VSMCs were stimulated with HMGB1 (10 to 500 ng/ml), IL-1β production was markedly increased. HMGB1 also increased the expression of NLRP3 inflammasome components including NLRP3, ASC and caspase-1. Among these components, HMGB1-induced expressions of NLRP3 and caspase-1 were markedly attenuated in TLR-2 siRNA-transfected cells, whereas ASC and caspase-1 expressions were reduced in RAGE-deficient cells. In TLR4-deficient cells, HMGB1-induced caspase-1 expression was significantly attenuated. Moreover, IL-1β production in HMGB1-stimulated cells was significantly reduced in cells transfected with caspase-1 siRNA as well as in cells treated with monoclonal antibodies or siRNAs for TLR2, TLR4 and RAGE. Overall, this study identified a pivotal role for NLRP3 inflammasome and its receptor signaling involved in the production of IL-1β in VSMCs stimulated with HMGB1. Thus, targeting HMGB1 signaling in VSMCs offers a promising therapeutic strategy for treating vascular remodeling diseases.